2007
DOI: 10.1002/ange.200701180
|View full text |Cite
|
Sign up to set email alerts
|

Assembly of Nanoparticle–Protein Binding Complexes: From Monomers to Ordered Arrays

Abstract: Gut definierte Monomere, Dimere, Trimere, dreidimensionale kugelförmige Schalen und zweidimensionale geordnete Anordnungen gentechnisch erzeugter Proteine wurden mithilfe funktionalisierter Goldnanopartikel hergestellt. Größe und Funktionalität der Nanopartikel sowie das Proteinmotiv tragen zur einzigartigen Geometrie und Orientierung, zur genauen stöchiometrischen Zusammensetzung und zur hohen Spezifität dieser Nanopartikel‐Protein‐Hybridstrukturen bei.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…1). Our previous results showed that the proteasomes were assembled into 2D arrays with a 1:1 stoichiometry between Au NP and proteasome when incubated with Ni-NTA Au NPs (Hu et al, 2007). In this study, image analysis showed that averaged top-view images from the proteasome arrays gave more accurate structural information at a higher resolution using fewer protein particles than those from the single particles without Au NPs.…”
Section: Introductionmentioning
confidence: 62%
See 2 more Smart Citations
“…1). Our previous results showed that the proteasomes were assembled into 2D arrays with a 1:1 stoichiometry between Au NP and proteasome when incubated with Ni-NTA Au NPs (Hu et al, 2007). In this study, image analysis showed that averaged top-view images from the proteasome arrays gave more accurate structural information at a higher resolution using fewer protein particles than those from the single particles without Au NPs.…”
Section: Introductionmentioning
confidence: 62%
“…Ni-NTA functionalized Au NPs were synthesized following our published method (Hu et al, 2007). In brief, hydrogen tetrachloroaurate (HAuCl 4 ) was reduced using sodium borohydride (NaBH 4 ) in the presence of L-glutathione (c-glu-cys-gly, GSH) and (1S)-N-[5-[(4-mercaptobutanoyl)amino]-1-carboxypentyl]iminodiacetic (Lys-NTA-SH) at pH 7.0, followed by treatment with a solution of NiCl 2 to convert Au NPs into Ni-NTA Au NPs.…”
Section: Synthesis Of Ni-nta Au Nps and Assembly Of Mtb 20s Proteasomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, several types of Au-NPs have been developed as labeling reagents for transmission electron microscopy (TEM) analysis of proteins. 8,[17][18][19][20][21][22][23][24][25][26] However, many of these do not meet our requirements for single protein TEM analysis. Desirable Au-NPs should be water soluble, stable in aqueous solution without forming a precipitate and have a modest diameter of 2-5 nm.…”
Section: Resultsmentioning
confidence: 99%
“…This is because a large number of NTA moieties per one gold particle lead to the assembly of proteins on the Au-NP through multiple crosslinking reactions. 24 Furthermore, because of the small size (1.4 or 1.8 nn on average), it is difficult to detect all Au-NPs directly in a TEM image.…”
Section: Resultsmentioning
confidence: 99%